Effects of six weeks of aerobic training on the resting levels of VEGF, Body Composition and VO2max within normobaric hypoxic conditions in overweight/obesity women - Atekeh Saidian; Rostam Alizadeh; Lida Moradi (Shahid Beheshti University, 2021)
Purpose: Since obesity and overweight have dramatically increased in recent years, the purpose of this study was to compare the effects of aerobic exercise training in normobaric hypoxia and normoxia conditions on the resting levels of the VEGF, body composition, and the VO2max among Overweight / Obesity Women. Methods: Twenty-four overweight women voluntarily agreed to take part in the study following the related announcement. The Mean±SD of their age, height, and weight were, respectively, 28.25 ± 3.7 (years), 161.8 ± 3.01 (cm), and 78.64 ± 7.18 (kg). The normobaric hypoxic training group performed aerobic training in hypoxic tents for six weeks, three sessions per week (with 60% of the maximum heart rate), and the normoxic group (control group) performed aerobic training for the same period of time as the hypoxic group. The training program included a 5-minute warm-up following 20 minutes of exercise at 60% of the maximum heart rate for the first week; every week, five minutes were added to the total exercise time. Results: The results of comparing pre- and post-exercise changes in body composition indexes for the normobaric hypoxic and normoxic groups indicated that changes in weight (p=0.165) and BMI (p= 0.191) were not significantly different, but the changes in fat percentage (p=0.022) and waist (p = 0.031) were significantly different between the two groups. The changes in the maximal oxygen consumption (p= 0.008) and the VEGF (p < 0.001) following six weeks of training also differed across groups. Conclusion: The significanlty larger increase in the resting levels of the VEGF in normobaric hypoxia conditions could indicate the importance of physical activity in such conditions in reducing the risk of cardiovascular diseases and vascular endothelial function among overweight people.